Financial factors influencing Profitability of Banque Pour Le Commerce Exterieur Lao Public (BCEL): https://doi.org/10.69692/SUJMRD0901256 - CHOUNLAMANY , Latsamy; CHANTHAVONE, Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The research aimed to investigate the financial factors that influencing profitability of Banque Pour Le Commerce Exterieur Lao Public (BCEL). The objectives of this study are 1) to examine the financial factors that influencing profitability of BCEL in long-term period, and 2) to examine the financial factors that influencing profitability of BCEL in short-term period. The research target group is BCEL, and the instrument used to collect data is the financial statement of the BCEL in the period of 2011-2020 (40 quarter), including capital structure, working capital, firm size, revenue growth rate and non-debt tax shield, which is to find out the financial factors that determine BCEL's profitability. The data of the research model was tested quantitatively by using Engle and Granger method and Error Correction model, which tested its stationary by unit root in Augmented Dickey-Fuller (ADF) test and multi-collinearity by used EViews 9 Program. The results found that the data of each financial factor is stationary in First Difference, except that revenue growth rate is stationary in level order at 99% significant. And firm size variables had been multi-collinearity, thus eliminating the revenue growth rate and the firm size variables from the model. Therefore, 1) the financial factors that influencing profitability of BCEL in long-term period was influenced by three factors the working capital, which has positive relationship with profitability of BCEL; the non-debt tax shield which has positive relationship with profitability of BCEL, capital structure which has negative relationship profitability of BCEL, 2)the financial factors that influencing profitability of BCEL in short-term period was influenced by three factors such as: the change of working capital which has positive relationship with the change of profitability of BCEL, the change of the non-debt tax shield which has positive relationship with the change of profitability of BCEL, the change of capital structure which has negative relationship with the change profitability of BCEL, and the short-term equilibrium deviates to the long-term equilibrium with a velocity of 88.64%.